Soluble adenylyl cyclase in nonmammalian sperm is directly controlled by pH, not by HCO 3 − or Ca 2+ - Olivia Kendall; Oanh Tu Hoang; Joshua L. Wort; Hussein Hamzeh; Heinz G. Körschen; René Pascal; Kai Korsching; Meritxell Wu-Lu; Wolfgang Bönigk; Christian Kambach; Luis Alvarez; Reinhard Seifert; et al. (Proceedings of the National Academy of Sciences, 2026)
In mammalian sperm, high HCO 3 − concentrations in semen and the oviduct activate soluble adenylyl cyclase (sAC), which synthesizes cyclic AMP to regulate sperm motility. Here, we demonstrate that sAC orthologs in echinoderms and fish, species whose sperm fertilize eggs in aquatic environments with low HCO 3 − , are activated by alkaline pH rather than HCO 3 − . In human sAC, two charged residues coordinate HCO 3 − and are essential for HCO 3 − -mediated activation. In contrast, pH-regulated sACs and orthologs from 13 phyla have these residues replaced by neutral ones. These substitutions abolish the enzyme’s responsiveness to HCO 3 − and suggest that pH regulation of sAC is widespread in nonmammalian metazoans. Furthermore, we show that in sea urchin sperm, a rise of pH during spawning stimulates cAMP synthesis, a key step in the activation of motility. An evolutionarily significant pattern is emerging: Across phyla, sAC regulation by pH or HCO 3 − represents an adaptation to environments with low or high HCO 3 − , respectively.